2017
DOI: 10.4088/jcp.16m11100
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Suicide Attempts Among Adolescents and Young Adults With Autism Spectrum Disorder

Abstract: Patients with ASD had an increased risk of suicide attempts compared with those without ASD. ASD was an independent risk factor of attempted suicide. Further studies are needed to clarify the underlying pathophysiology between ASD and suicidality and to elucidate whether prompt intervention for ASD may reduce this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 0 publications
7
83
4
2
Order By: Relevance
“…While autism is often and should be diagnosed in childhood, increasing research has focussed on the long-term mental and physical health of autistic individuals throughout adulthood. Specifically, a growing body of research has identified that autistic adults are at higher risk for SSBI [1][2][3][4][5][6] and life-long vulnerability [91]. These studies are all limited in that they have tested relatively small cohorts, and have typically relied on clinical groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While autism is often and should be diagnosed in childhood, increasing research has focussed on the long-term mental and physical health of autistic individuals throughout adulthood. Specifically, a growing body of research has identified that autistic adults are at higher risk for SSBI [1][2][3][4][5][6] and life-long vulnerability [91]. These studies are all limited in that they have tested relatively small cohorts, and have typically relied on clinical groups.…”
Section: Discussionmentioning
confidence: 99%
“…Autistic individuals have elevated rates of self-harm (with or without suicidal intent) and suicidal behaviour and ideation (SSBI) [1][2][3][4][5][6]. In addition, there is a positive association between autistic traits (subclinical manifestation of autism features) and SSBI [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…The SBQ-ASC has 5 scored items (Table 2). Item 1 assesses lifetime experience of suicidal thoughts and behaviours from "Never" (0) to "I have attempted to end my life" (4). Item 2 assesses frequency of intense suicidal thoughts in the last 12 months from "Never" (0) to "1 or more times a day" (6).…”
Section: Methodsmentioning
confidence: 99%
“…People diagnosed with autism (henceforth autistic people [1]) are at signi cantly increased risk of experiencing suicidal thoughts and behaviours [3][4][5] and death by suicide [6][7], compared to non-autistic people. Autistic people who have experienced delay in autism diagnosis until adulthood show the highest estimates of lifetime suicidal thoughts (66%), and suicide attempt(s) (35-36%) [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Traits characteristic of autism are also significantly associated with suicidality in those with [ 2 ], and without ASC diagnosis [ 16 18 ]. ASC diagnosis has also recently been found to be an independent risk marker for suicide attempts independent of demographic characteristics and co-occurring diagnoses [ 19 ]. These findings suggest that ASC explains additional variance in suicidality, not accounted for by other well-known risk markers in the general population which are more prevalent in ASC, such as depression [ 20 22 ] or social isolation [ 23 , 24 ], which have been associated with increased risk of suicidality in ASC [ 2 , 15 , 17 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%